2019
DOI: 10.15244/pjoes/93293
|View full text |Cite
|
Sign up to set email alerts
|

The Snow Vole and Tatra Marmot as Different Rodent Bioindicators of Lead Pollution in an Alpine Environment: A Hibernation Effect

Abstract: Alpine ecosystems are the main accumulation sites of trace metals from the atmosphere [1-2]. According to studies on alpine-like sediments in the Eastern Tibetan Plateau, anthropogenic metals began to appear around 1950, significantly increased in the 1980s, and peaked in the mid-1990s. Over 80% of Cd, Pb and Zn were quantified from anthropogenic emissions in atmospheric deposition since the mid-1990s atmosphere [3]. In Europe, the Western Carpathians are one of the most lead-polluted alpine regions [4]. Seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
7
1
Order By: Relevance
“…Potential sources of heavy metals in the Tatra mountains may be northern Moravia in the Czech Republic and the Małopolska district in southern Poland with Zn-Pb mines and smelters [48][49][50][51]. In addition, our previous studies show high levels of Zn were found in the bones and teeth of Tatra marmots, with this element being detected in all samples [38,52]. In a study of snow voles from the Tatra mountains, Zn was also found in all samples, and the mean amount of Zn in bone tissues was 72.49 ppm ± 24.76 [53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Potential sources of heavy metals in the Tatra mountains may be northern Moravia in the Czech Republic and the Małopolska district in southern Poland with Zn-Pb mines and smelters [48][49][50][51]. In addition, our previous studies show high levels of Zn were found in the bones and teeth of Tatra marmots, with this element being detected in all samples [38,52]. In a study of snow voles from the Tatra mountains, Zn was also found in all samples, and the mean amount of Zn in bone tissues was 72.49 ppm ± 24.76 [53].…”
Section: Discussionmentioning
confidence: 99%
“…Due to weathering and hydrologic cycles, Sr from these rocks penetrates into soils, plants, and subsequently into animal skeletons [61]. In bones, Sr is highly related to P content [38]. It was found that Sr in bones decreases as dietary phosphorus increases [62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrations of Pb and Cd in Vaccinium myrtillus, Luzula luzuloides and Dryopteris dilatata have mostly been found to exceed the limits of the natural occurrence of these elements in plants (Ciriaková, 2009 ). The alpine biota in the Tatras is probably under permanent, long-term stress from exposure to TMs, as suggested by the excessive amounts of Zn, Pb and Cd reported from the skulls, bones, and teeth of wild animals, such as snow voles, Tatra marmots and chamois (Ballová et al, 2019 ; Janiga & Haas, 2018 ; Janiga et al, 2019 ). However, the pollution of the TNP environment is primarily a sad remnant of the strong development of heavy industry and mining in Poland in the 1970s, with influxes of pollutants also taking place in later years.…”
Section: Discussionmentioning
confidence: 99%
“…interecosystem nutrient transfer, high consumption rates and large body sizes; e.g. El-Sabaawi, 2017;Janetski et al, 2009;May & El-Sabaawi, 2022) and the major declines in vertebrate diversity and abundance in recent history (e.g. Hoffmann et al, 2010;Kiesecker et al, 2001;Rodrigues et al, 2014), this is essential.…”
mentioning
confidence: 99%